2017
DOI: 10.1111/jcpp.12794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal alcohol consumption on cognitive development and ADHD‐related behaviour in primary‐school age: a multilevel study based on meconium ethyl glucuronide

Abstract: Associations between EtG and cognitive deficits, attentional resource capacity and ADHD-related behaviour could be documented with effects that were partially dose-dependent. In addition to maternal self-reports, this biomarker of intrauterine alcohol exposure may be considered as a predictor of child development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 35 publications
4
38
0
Order By: Relevance
“…Moreover, the observed differences in the Go-P3 ( Eichler et al, 2018 ) as reported recently were also stable using the threshold of EtG ≥ 30 ng/g ( Table 1 ). The differences between the EtG+ group ( n = 31) and controls ( n = 117) were analyzed by t -test ( t = 2.43, p = 0.004, d = 0.49).…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Moreover, the observed differences in the Go-P3 ( Eichler et al, 2018 ) as reported recently were also stable using the threshold of EtG ≥ 30 ng/g ( Table 1 ). The differences between the EtG+ group ( n = 31) and controls ( n = 117) were analyzed by t -test ( t = 2.43, p = 0.004, d = 0.49).…”
Section: Resultssupporting
confidence: 78%
“…Using the FRANCES cohort, Eichler et al (2018) showed IQ differences in children with an EtG concentration in meconium above the 50th percentile. Here, we report this effect to be also persistent in the group of the EtG positive children with a threshold set at ≥30 ng/g.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations